PENGARUH PROFITABILITAS DAN FINANCIAL LEVERAGE PADA COST OF DEBT DENGAN EARNINGS MANAGEMENT SEBAGAI VARIABEL PEMODERASI - Renny Muspyta; Herman Ruslim (Jurnal Kontemporer Akuntansi, 2023)
This study aims to determine the effect of profitability and financial leverage on the cost of debt, and the role of earnings management as a moderating variable. In this study, profitability is measured by the Ratio of return on equity, financial leverage is measured by the proxy debt Ratio, earnings management as measured by discretionary accruals, and cost of debt is measured by the Ratio of interest expense divided by the average total debt. The population in this study are publicly traded companies listed on the IDX, and the sample used is manufacturing companies listed on the IDX for the 2016-2019 period. Based on the purposive sampling method, the samples obtained were 69 manufacturing companies and 276 observations. The results showed that profitability has a negative effect on the cost of debt, while financial leverage has no effect on the cost of debt, earnings management cannot weaken the negative effect of profitability on the cost of debt and earnings management cannot weaken the negative effect of financial leverage on the cost of debt.